ISOLASI DAN KARAKTERISASI KEMAMPUAN BAKTERI ENDOFIT SORGUM MANIS FS501 SEBAGAI PENDUKUNG PERTUMBUHAN TANAMAN - Charlie Ester de Fretes (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2020)
This study aims to isolate endophytic bacteria of sweet sorghum plants and characterize their ability as plant growth promoting. The characters tested in this study were the ability of endophytic bacteria in N fixation, phosphate dissolving, and IAA production to be developed as biological fertilizer agents. Twenty-four isolates were isolated from the roots, stems and shoots of sweet sorghum. The results of bacterial DNA fingerprint screening showed that 11 groups of endophytic bacteria had different fingerprints. Isolates capable of N fixation were grown on LGI media and showed a change in the color of the medium. The nifH gene detection is also carried out to determine endophytic diazotrophic bacteria. Isolate bacteria that can dissolve inorganic phosphate were tested using Pikovskaya media. Testing the ability of isolates to produce IAA was carried out by adding Salkowski's reagent to the bacterial culture and measured quantitatively with a λ 530 nm spectrophotometer. The results showed that two endophytic bacterial isolates proved to be diazotrophic and three isolates were able to dissolve phosphate, while one isolate was able to produce IAA. PA2 isolate showed ability in all the characters tested, namely N fixation, phosphate solvent and IAA producer.